The Influence Of Services, Tax Sanctions, Participation Strategies, And The Role Of Religion On Regional Taxpayer Compliance - Rachmad Robbi; Windhu Putra; Elyta Elyta; Irfan Mahdi (International Journal of Business and Quality Research, 2024)
This research investigates the factors that influence taxpayer compliance in an economic context, focusing on aspects of tax services, tax sanctions, government strategy, and religion. Through factor analysis and structural equation modeling, this research reveals five main findings: 1) Tax officer service quality has a positive and significant influence on taxpayer compliance, including aspects such as ease of payment and availability of information. 2) Tax sanctions have a positive effect on tax compliance, in line with deterrence theory and social behavior. 3) Government participation strategies may not be effective in increasing tax compliance but are still relevant as part of broader efforts. 4) Religion has a positive influence on tax compliance, supported by various theories such as social and moral values. 5) Structural equation models are used to describe the relationship between these variables and show the influence of each on tax compliance. These findings provide new insights into how governments can improve tax compliance through various approaches, and emphasize the importance of quality services and appropriate application of sanctions.